Anti-proliferative and apoptosis-inducing effects of Morinda citrifolia L. shoot on breast, liver, and colorectal cancer cell lines - Meli, Mohd Amir Ashraf; Shafie, Nurul Husna; Loh, Su Peng; Rahmat, Asmah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Morinda citrifolia or also known as noni is commonly consumed raw or blanched as side dishes or ‘ulam’. As cancer is one of the most leading causes of death in the world, we aimed to evaluate the anti-proliferative potential of noni shoot against various types of cancer cell lines. Methods: The breast cancer (MDA-MB-231), liver cancer (HepG2), and colorectal cancer (HT-29) cell lines were treated with 70% ethanol extract of noni shoot for cytotoxicity testing using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Apoptosis induction effects were examined using AO/PI dual fluorescent assay and cell cycle analysis using flow cytometry. Gas chromatography-mass spectrometry (GCMS) was also carried out to characterize the active compounds in noni shoot. Results: The cytotoxicity assay demonstrated noni shoot had IC50 of 49.72 μg/mL, 307.5 μg/mL and 65.43 μg/mL against MDA-MB-231, HepG2, and HT-29 cell lines, respectively. The AO/PI staining showed apoptotic bodies such as cell blebbing, chromatin condensation, and nuclear fragmentation was markedly induced in the selected cancer cell lines-treated with noni shoot extract. Apoptosis induction by noni shoot was showed by a significant increase in sub G0/G1 phase in MDA-MB-231 and HT-29 cell lines of cell cycle analysis. It was found that noni shoot extract contained mostly acetic acid and ethriol that may contribute to its anti-cancer properties. Conclusion: These findings showed the potential anticancer properties of noni shoot extract thereby, further studies are needed to understand the mechanism of noni as anti-cancer agent and possibility to be developed as a nutraceutical or functional food products.